2018
DOI: 10.1021/acs.biochem.8b00560
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Assembly, and Disassembly of Tubulin Single Rings

Abstract: Single and double tubulin rings were studied under a range of conditions and during microtubule (MT) assembly and disassembly. Here, tubulin was purified from porcine brain and used without any further modifications or additives that promote ring assembly. The structure of single GDP-rich tubulin rings was determined by cryo-transmission electron microscopy and synchrotron solution X-ray scattering. The scattering curves were fitted to atomic models, using our state-of-the-art analysis software, . We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(82 citation statements)
references
References 73 publications
3
78
0
Order By: Relevance
“…Sample preparation. Stored tubulin was thawed on ice, after which three polymerization/depolymerization cycles (at 36°C and 0 °C, 30 min each) were performed to obtain GDP-rich tubulin (about 80% of the exchangeable sites contained GDP, determined using published protocols 28,39 ). The tubulin was then centrifuged for 30 min at 15,700 g and 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation. Stored tubulin was thawed on ice, after which three polymerization/depolymerization cycles (at 36°C and 0 °C, 30 min each) were performed to obtain GDP-rich tubulin (about 80% of the exchangeable sites contained GDP, determined using published protocols 28,39 ). The tubulin was then centrifuged for 30 min at 15,700 g and 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…. The different time-resolved data sets of each reaction showed that repeated exposure to the X-ray beam triggered disassembly of relatively small tubulin structures 28 (tubulin oligomers, THPs or TCSs subunits), which slowed down the assembly kinetics. As at least two identical time sets (delays and intervals) were used in all of the reaction conditions (4 mg/ml tubulin with 1, 5, or 20 mM spermine), we were able to compare the reaction rates.…”
Section: Methodsmentioning
confidence: 99%
“…A well-known example is the study of muscle contraction along the pathway of physiological activation [79]. During this decade, TR-SAXS enabled probing in depth the self-assembly of virus particles [80,81], tubulin single rings [82], etc. from their constituting subunits.…”
Section: Assembly Of Biomacromolecular Complexesmentioning
confidence: 99%
“…Microtubules preparation. Black tubulin from porcine brain, purified via three polymerization/depolymerization cycles (65), was kindly provided by Uri Raviv (Hebrew University). Purified tubulin was flash-frozen in liquid nitrogen and kept at -80˚C until used.…”
Section: Motility Assay Experimentsmentioning
confidence: 99%